Survey of suicide attempts in sari. - Susan Afghah; Morteza Aghahasani; Morteza Noori-Khajavi; Emytis Tavakoli (Iranian Journal of Psychiatry, 2014)
Objective: Studying suicide can be of assistance to prepare the ground for the adoption of effective preventative measures. In the present study, our aim was an in-depth review of suicide epidemiology in the city of Sari, in the northern part of Iran. Our focus was on geo-demographic and other risk factors affecting the frequency of suicide in order to demonstrate populations with greater risk of suicide for future preventive and protective measures. Method: In a prospective study, during a one year period, a descriptive semi-structured questionnaire was used to conduct interviews with subjects who attempted suicide and referred to one of the four major trauma and emergency centers in the city of Sari, or with the relatives of those who completed their attempt. Convenience sampling method was used. Statistical analysis was performed using SPSS-20 software. Multivariate tests were based on χ2 values. Logistic regression was performed estimating the effect of risk -factors. Results: In this study, 228 suicide a tempters were enrolled; of whom, 78.5% were female; 28.5% of all the attempts resulted in death. The odds of suicide completion were significantly increased in the following cases: married status (OR: 3.49; 95% CI 2.82,4.53), illiteracy (OR:2.71;95%CI 2.10,3.64), presence of comorbid physical illness (OR:2.22;95%CI 1.64,3.21), history of previous suicide attempt (OR:2.03; 95%CI 1.56,2.81), and age over 50 (OR: 2.01, 95% CI 1.14,3.05). Suicide outcome estimated worst in the married illiterate atte mpters. The leading method of use was suicide by burn (SBB). Conclusion: The variety observed in the regional distribution of suicide risk factors calls for more non-discriminatory attention and adoption of precautionary, preventative and protective measures for each section of the society accordingly.